Über den Zusammenhang von Tragfähigkeitsmessergebnissen mit mechanischen Modellgrößen bei Asphaltstraßen - Plachkova-Dzhurova, Plamena Nedeva (Veröffentlichungen des Institutes für Straßen- und Eisenbahnwesen, 2017)
This work examines the mechanical deformation of flexible pavement under vertical load. Mechanical approaches for the computation of the radius of curvature R0 at the centre of the loaded area from HWD data were developed. Material parameter have been backcalculated in an iterative way using rheological models After that the radius of curvature has been subsequently calculated based on mechanical systems.